Haptic PIVOT: On-Demand Handhelds in VR - Kovacs, Robert; Ofek, Eyal; Siu, Alexa Fay; Marwecki, Sebastian; Holz, Christian; Sinclair, Mike; Gonzalez Franco, Mar (UIST 2020, 2020)
We present PIVOT, a wrist-worn haptic device that renders virtual objects into the user’s hand on demand. Its simple design comprises a single actuated joint that pivots a haptic handle into and out of the user’s hand, rendering the haptic sensations of grasping, catching, or throwing an object – anywhere in space. Unlike existing hand-held haptic devices and haptic gloves, PIVOT leaves the user’s palm free when not in use, allowing users to make unencumbered use of their hand. PIVOT also enables rendering forces acting on the held virtual objects, such as gravity, inertia, or air-drag, by actively driving its motor while the user is firmly holding the handle. When wearing a PIVOT device on both hands, they can add haptic feedback to bimanual interaction, such as lifting larger objects. In our user study, participants (n=12) evaluated the realism of grabbing and releasing objects of different shape and size with mean score 5.19 on a scale from 1 to 7, rated the ability to catch and throw balls in different directions with different velocities (mean=5.5), and verified the ability to render the comparative weight of held objects with 87% accuracy for 100g increments.